Using two or more complete sentences, describe and correct the error in the solution. Solve the system of equations. 3

Question

Using two or more complete sentences, describe and correct the error in the solution.

Solve the system of equations.

3x – 2y = 2

9x – 6y = 6

3x – 2y = 2 → 9x – 2y = 6
9x – 6y = 6 → 9x – 6y = 6
-8y = 12
y = 1.5
3x – 2y = 2 → 3x – 2(1.5) = 6
3x – 3 = 6
3x = 9
x = 3​

in progress 0
Diễm Thu 3 months 2021-07-25T02:42:20+00:00 1 Answers 1 views 0

Answers ( )

    0
    2021-07-25T02:43:47+00:00

    Answer:

    In the very first step, when they multiply both sides by 3 the -2y should become -6y but instead it stays as -2y. The correct solution would be:

    9x – 6y  =6

    9x – 6y = 6

    0 = 0

    This means there are infinite solutions.

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )